2020
DOI: 10.1093/ons/opaa123
|View full text |Cite
|
Sign up to set email alerts
|

Frameless Stereotactic Brain Biopsies: Comparison of Minimally Invasive Robot-Guided and Manual Arm-Based Technique

Abstract: BACKGROUND Most brain biopsies are still performed with the aid of a navigation-guided mechanical arm. Due to the manual trajectory alignment without rigid skull contact, frameless aiming devices are prone to considerably lower accuracy. OBJECTIVE To compare a novel minimally invasive robot-guided biopsy technique with rigid skull fixation to a standard frameless manual arm biopsy procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…8 Recently, with the advancement of neuronavigation technologies, frameless stereotactic brain biopsy and robot-assisted stereotactic brain biopsy have been introduced. [38][39][40][41] Recent studies have reported that the stability and efficiency of these new technologies are equivalent to those of standard frame-based stereotactic biopsy. We have also started using robot-assisted surgery to implant electrodes in patients with epilepsy, with accuracy and safety similar to those of conventional stereotactic procedures.…”
Section: Stereotactic Biopsy Techniquementioning
confidence: 99%
“…8 Recently, with the advancement of neuronavigation technologies, frameless stereotactic brain biopsy and robot-assisted stereotactic brain biopsy have been introduced. [38][39][40][41] Recent studies have reported that the stability and efficiency of these new technologies are equivalent to those of standard frame-based stereotactic biopsy. We have also started using robot-assisted surgery to implant electrodes in patients with epilepsy, with accuracy and safety similar to those of conventional stereotactic procedures.…”
Section: Stereotactic Biopsy Techniquementioning
confidence: 99%
“…reported a series of 40 cases of frameless stereotactic biopsies and compared a minimally invasive robotic technique using the iSYS1 robot (iSYS Medizintechnik GmbH) with a manual arm‐based technique. Using robotic technique the mean EPE was 1.5 mm (range 0.4–3.2 mm) while the mean TPE was 1.5 mm (range 0.4–2.8 mm) 44 . Spyrantis et al.…”
Section: Discussionmentioning
confidence: 97%
“…Nowadays, similar systems have gained a pivotal role during cranial and spinal surgeries to facilitate safer and more accurate, minimally invasive procedures, as well as to provide the best possible approaches and less time-consuming interventions ( 12 ). Hence, the majority of brain tumor biopsies are now executed using a frameless navigation-guided automated arm ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such systems minimize movement and increase stability while bone drilling, perform accurate skin and cortical incision placement, and specify drilling depth based on measurement of the skull thickness, enabling real-time visualization 35 . Several studies have reported a 95% up to 100% diagnostic accuracy from robot-assisted brain biopsy 9,13,36 , resulting in con-siderably lower target errors when compared to standard manual brain biopsy techniques 37 , showing markedly shorter median surgical time, and evidently lower complication rates 9,13,23,[36][37][38] . Accordingly, all samples were positive for tumor tissue, the iatrogenic cortical damage was minimal, and no procedure-related shortterm complications were recorded in the series of our patients.…”
Section: Discussionmentioning
confidence: 99%